The Hidden Meaning of Household Accounting Implementation Among Moslem Accountants - Dwiya Endah Pandu Probowati; Anis Chariri; Jaka Isgiyarta (Universitas Budi Luhur, 2023)
The purpose of this study was to find the hidden meaning of the implementation of household accounting among moslem accountant. This research using qualitative interpretive method - case study with primary data acquisition techniques using observation and direct interview. This research founds that the implementation of household accounting is motivated by the the goal of marriage namely, samawa. While the the mental accounting concept, the type of internal locus of control and Islamic religious values creates spiritual intelligency and awareness for running the household away from waste and irrational spending. The implementation of household accounting creates mutual trust among husband and wife because there is no financial related activities hiden. Another findings of this research is the form of financial report among informants are varies based on each unique condition of the household, the simplest form is using book-based financial records while the more modern ones use spreadsheets. Keywords: Accountability, Budgeting, Mental accounting, Locus of control, Household accounting